2022
DOI: 10.3390/ani12101298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Black Cumin Seeds (Nigella sativa) on Performance, Carcass Traits, and Meat Quality of Japanese Quails (Coturnix coturnix japonica)

Abstract: The current study was conducted to determine the effect of adding black cumin (Nigella sativa) powder (BCP) to the Japanese quail diet on the carcass characteristics and meat quality. In this research, 240 Japanese quail chicks (mean initial body weight 9.15 ± 0.12) were divided into four groups of four replications each. Treatments consisted of the addition of BCP at levels 1, 2, and 4% to the mixed feed and control group without the BCP additive. Compared to the other groups, the group with the 2% BCP diet h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Similarly, Hannan et al described the stimulating role of N. sativa bioactive compounds on digestion [ 50 ]. This could be attributed to its role as a strong stimulant on digestive enzymes [ 51 ] and its potency in increasing the retention of nutrients with a positive reflection on their utilization. Moreover, the promising effects of N. sativa on growth performance are assumed to be due to its high nutritive value along with its pharmacologically active compounds [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hannan et al described the stimulating role of N. sativa bioactive compounds on digestion [ 50 ]. This could be attributed to its role as a strong stimulant on digestive enzymes [ 51 ] and its potency in increasing the retention of nutrients with a positive reflection on their utilization. Moreover, the promising effects of N. sativa on growth performance are assumed to be due to its high nutritive value along with its pharmacologically active compounds [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of black cumin produced highest body weight compared with all other treatments, better FCR than control, good dressing percentage and higher gizzard and intestinal weights than control in this study (Arif et al 2019;Aydogan et al 2020;Haq et al 2020;Devi et al 2022;Asghar et al 2022). Black cumin seeds have been used as a natural growth promoter in many trials of broiler and they were found to boost body weight (El-Ghammry et al 2002;Hassan et al 2004), FCR (Takruri and Dameh 1998;Abu-Dieyeh and Abu-Darwish 2008) and carcass characteristics (Guler et al 2006;Toghyani et al 2010).…”
Section: Discussionmentioning
confidence: 60%
“…The enhancement in sucrase and maltase activities could beneficially influence the digestion of carbohydrates in the gastrointestinal tract ( Yang et al, 2019 ). Additionally, previous studies stated that EOs had a stimulating role in the digestive system, which lead to better absorption and performance of broilers ( amroz, 2002 ; Asghar et al, 2022 ). This could be explained by their great enhancing effects on digestive enzymes ( Asghar et al, 2022 ) and their effectiveness in enhancing the retention and utilization of nutrients ( Elmowalid et al, 2022 ), which are resulted from their incorporation in liposomes particles ( de Souza et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%